The Effect Model of Problem Based Learning in Social Science Subject - Miftahul Jannah; Sugiharto Sugiharto; Abdul Murad (Randwick International of Education and Linguistics Science Journal, 2023)
This research aims to determine: 1) the influence of the Problem Based Learning model on the social studies learning outcomes of students who have high learning motivation and low learning motivation. 2) Knowing the interaction between the Problem Based Learning model and learning motivation on social studies learning outcomes in elementary school. This research uses quasi-experimental research methods. The population of this research was 54 fourth grade students at SD IT Darul Fikri. The research sample was class IVa with 27 students as the experimental class and class IVb with 27 students as the control class. Data collection techniques use learning motivation questionnaires and learning outcomes tests. The data analysis technique uses two-way Anova. The research results are as follows: (1) there is a significant difference between the learning outcomes of experimental class students with high learning motivation with an average of 95 and students who have low learning motivation with an average of 80, while the learning outcomes of dick class students with high learning motivation with an average of 92 and students who have low learning motivation with an average of 74.76, the significance value is 0.000, so that the test results (sig) <significance level, namely 0.000<0.050, then H0 is rejected. (2) there is an interaction between the Problem Based Learning model and student learning motivation in improving students' social studies learning outcomes. The results of the analysis show the significance value of the interaction is 0.004. This value is smaller than the predetermined significance level, namely 0.05. The calculated F value is 1.234, so Ha is accepted and Ho is rejected.